2015
DOI: 10.1038/onc.2015.435
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-16 mediates the regulation of a senescence–apoptosis switch in cutaneous T-cell and other non-Hodgkin lymphomas

Abstract: Multiple sequential genetic and epigenetic alterations underlie cancer development and progression. Overcoming cellular senescence is an early step in cancer pathogenesis. Here, we demonstrate that a noncoding regulatory RNA, microRNA-16 (miR-16), has the potential to induce cellular senescence. First, we examined the expression of miR-16 in primary cutaneous T-cell lymphoma (CTCL) and other non-Hodgkin T/natural killer (NK)-cell lymphomas and found that miR-16 was downregulated than that in the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 45 publications
5
47
0
3
Order By: Relevance
“…Tissue samples were obtained from the metastatic lymph nodes of primary cases. Among the four CTCL cell lines, we previously demonstrated that the subcutaneous injection of My-La, HH, and HUT78 into NOD/Shi-scid IL-2γnul mice induced multiple metastases in various visceral organs [10, 11, 18]. Here, we confirmed there was an increased expression of HDACs (1, 2, 3, 4, and 6) and CCR6 in the CTCL cell lines and primary tissue samples (Figure 1A).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Tissue samples were obtained from the metastatic lymph nodes of primary cases. Among the four CTCL cell lines, we previously demonstrated that the subcutaneous injection of My-La, HH, and HUT78 into NOD/Shi-scid IL-2γnul mice induced multiple metastases in various visceral organs [10, 11, 18]. Here, we confirmed there was an increased expression of HDACs (1, 2, 3, 4, and 6) and CCR6 in the CTCL cell lines and primary tissue samples (Figure 1A).…”
Section: Resultssupporting
confidence: 77%
“…Along with inhibition of cell proliferation, miR-16 induced apoptosis or cellular senescence [18]. In this study, we also demonstrated that the induction of apoptosis or senescence was dependent on p53 status: miR-16 induced apoptosis in p53-mutated CTCL, but senescence in the p53 wild-type.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…In addition, miR-15b was a negative regulator of stress-induced SIRT4 expression thereby counteracting senescence associated mitochondrial dysfunction and regulating the senescence-associated secretory phenotype (SASP) and possibly organ aging, such as photoaging of human skin (Lang et al, 2016). Another study had shown forced expression of miR-16 could enhance p21 expression via down-regulation of the polycomb group protein Bmi1, thereby inducing cellular senescence (Kitadate et al, 2016). However, There were still no evidences whether the expression of hsa-miR-16-5p, hsa-miR-26b-5p, hsa-miR-15b-5p, hsa-miR-15a-5p changed with human brain aging.…”
Section: Resultsmentioning
confidence: 99%